IMPLEMENTASI FRAUD TRIANGLE DALAM MENDEKTESI FRAUD (KANTOR AKUNTAN PUBLIK RAZIKUN TARKOSUNARYO TB. SIMATUPANG) - Karlina, - (2019)
This research was conducted to analyze the implementation of fraud in implementing fraud at Razikun Tarkosunaryo's Public Accounting Firm. This study uses interview and observation methods in obtaining data and information for analysis. Based on the results of research at Razikun Tarkosunaryo Public Accountant Office that has been able to implement triangle fraud. This study uses qualitative methods with interprentive paradigms with ethnometodology approaches. The data analysis technique used is source triangulation by conducting interviews with key informants and supporting informants and by collecting documents as supporting data. The results of this study indicate that (1) The implementation of the Fraud Triangle has now been implemented in KAP Razikun Tarkosunaryo (2) and to detecting fraud in KAP companies Razikun Tarkosunaryo has implemented or followed Audit Standards 240 and analytical procedures to detecting fraud